Extensive cerebrovascular disease and stroke with prolonged prodromal symptoms as first presentation of perinatally-acquired human immunodeficiency virus infection in a young adult. (May 2018) - Chigonda, TG; Chatora, GT; Ngwende, GW; Miller, RF; Ferrand, RA
A 26-year-old black African woman presented with an acute onset of hemiparesis and visual symptoms. This had been preceded several months by symptoms which were apparently psychiatric in nature. She had no apparent risk for cerebrovascular disease. Neurological evaluation revealed a striking burden of cerebrovascular disease for her age, including the rare stroke syndrome of basilar artery occlusion. Human immunodeficiency virus (HIV) infection was identified during clinical assessment. This was judged to be perinatally acquired, as there was no history of sexual debut or blood transfusion; her mother was taking antiretroviral therapy and she had facial planar warts and underlying bronchiectasis. Therefore, it has been concluded that presentation of stroke should prompt HIV testing in young people and perinatally-acquired infection can present in adulthood.